Ellagic acid alleviates NLRP6/caspase-1/GSDMD-mediated inflammation and pyroptosis in rats post cerebral ischemia/reperfusion injury - Ling Hu; Xiaoqiong Wei; Guofu Shen; Xiaohuan Huang (Iranian Journal of Basic Medical Sciences)
Objective(s): Ellagic acid (EA) is a natural polyphenol with anti-cancer, anti-oxidant, anti-inflammatory, antibacterial, and other effects. However, the role of EA in cerebral ischemia/reperfusion injury (CIRI) remains unclear. This study aims to investigate the neuroprotective effects of EA in CIRI.Materials and Methods: Forty male Wistar rats (260-300 g) were randomly divided into four groups with 10 rats per group: 1) Sham+Veh: Rats underwent I/R surgery, except that they were not inserted with thread plugs, and received solute treatment at the same time. 2) MCAO/R+Veh. 3) MCAO/R+EA: Rats were administered 200 mg/kg EA before undergoing MCAO. 4) MCAO/R+Nim: Rats were administered Nim before undergoing MCAO.Results: Cerebral MCAO/R damaged brain tissue, elevated neurological deficit score (P<0.01), cerebral infarction volume (P<0.01), inflammatory cell infiltration (P<0.01), NLRP6, ASC, caspase-1 and GSDMD mRNA level (P<0.01 and P<0.001), NLRP6, caspase-1, GSDMD-N and IL-1β protein level (P<0.01 and P<0.001), and inflammatory cytokines in brain tissue (P<0.01). Prophylactic administration of EA also significantly improved brain tissue damage, reduced neurological deficit score (P<0.01), cerebral infarction volume (P<0.01), inflammatory cell number (P<0.05), NLRP6, caspase-1, GSDMD-N mRNA and protein level (P<0.05 and P<0.01), ASC mRNA level and IL-1β protein level (P<0.01), and IL-1β and IL-18 level in brain tissue (P<0.01) compared to positive control.Conclusion: EA may serve as a potential drug for the treatment of brain I/R, which may exert an anti-inflammatory effect by inhibiting the activation of the inflammasome.